1986
DOI: 10.1038/ki.1986.242
|View full text |Cite
|
Sign up to set email alerts
|

The effects of metabolic acidosis on bone formation and bone resorption in the rat

Abstract: Metabolic acidosis (MA) has been implicated in the pathogenesis of both osteomalacia and osteopenia. Alterations in the secretion of parathyroid hormone and in the metabolism of vitamin D may contribute to such skeletal changes. To minimize the influence of these factors, quantitative bone histology and measurements of bone formation using double tetracycline labeling were done in thyroparathyroidectomized (TPTX) rats with MA induced by ammonium chloride (TPTX-A), and in both non-acidotic TPTX (TPTX-C) and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(78 citation statements)
references
References 33 publications
4
74
0
Order By: Relevance
“…Benzoic acid is the only organic acid in pig nutrition which reduces urinary pH through its metabolic end product hippuric acid. This acidification is why more Ca is excreted in urine to re-establish the acid-base balance of the body as it is reported in rats (Kraut et al, 1986). In this study, this effect was observed in the reduced Ca content in MT of the younger pigs.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Benzoic acid is the only organic acid in pig nutrition which reduces urinary pH through its metabolic end product hippuric acid. This acidification is why more Ca is excreted in urine to re-establish the acid-base balance of the body as it is reported in rats (Kraut et al, 1986). In this study, this effect was observed in the reduced Ca content in MT of the younger pigs.…”
Section: Discussionsupporting
confidence: 63%
“…Benzoic acid as a feed additive has been authorized in the European Union since May 2003 [Commission Regulation (EC) 877/2003;European Union, 2003] and is now listed in the group of zootechnical additives (EC 1138(EC /2007European Union, 2007). The acidification of diet and gastrointestinal tract can cause an increased renal mineral excretion and, thus, reduce bone mineralization (Kraut et al, 1986). It is unclear whether 4 these effects can be avoided with the addition of Phy but results in the study by Radcliffe et al (1998) indicate such a protective effect.…”
Section: Introductionmentioning
confidence: 75%
“…Indeed, bone mineral, especially carbonate, has been reported to decrease during metabolic acidosis (66,71,72), and provision of bicarbonate increases bone mineral (73,74). In vitro metabolic acidosis increases Ca efflux from bone both by promoting physicochemical mineral dissolution within hours (13), especially of CaCO 3 (21), and by enhancing osteoclastic bone resorption over longer periods (13).…”
Section: Metabolic Acidosismentioning
confidence: 99%
“…It is well recognized that children with chronic metabolic acidosis and normal renal function have poor growth, and in vitro studies have shown that metabolic acidosis is associated with a decrease in bone mineralization [16]. Thus, current Kidney Disease Outcomes Quality Initiative (K/DOQI) nutritional guidelines for children recommend maintaining a serum bicarbonate level >22 mmol/L [17].…”
Section: Discussionmentioning
confidence: 99%